Approaching climate change mitigation policymaking in South Africa: a view from critical complexity thinking. (25th November 2020) - Tyler, Emily; Cohen, Brett
ABSTRACT: From a complexity thinking perspective, the world is understood as complex, systemic, and only partially knowable. The particular perspective we inhabit is determinant of what we can know. Perspective or 'approach' is therefore foregrounded by complexity thinkers as an active part of knowing and acting. We take a complexity view of climate change mitigation policymaking to argue that climate change mitigation policy communities have a dominant approach, which determines both our understanding of the climate change mitigation policy problem, and how we respond to it. To construct this argument, we first summarize and describe the existence of a hegemonic scientific and cultural worldview. We use multi-disciplinary literatures to demonstrate how this worldview operates in the approach of the international climate change mitigation policy community. Finally, we draw on empirical datasets to describe how the influence of this worldview characterizes the dominant approach of the South African climate change mitigation policy community. That climate change mitigation policy communities have a dominant approach means that, whilst aspects of the complex policy situation are illuminated by this approach, others are obscured. It is clear from the Intergovernmental Panel on Climate Change report on 1.5°C warming that policymakers are not yet responding adequately to the problem. If approach determines what we see and how we act, it follows that approach can be interrogated as an active site of the policy challenge. A complexity view, for instance, enables us to see differently, emphasizing perspective, impartial knowledge, non-linearities and emergence in complexity and complex systems. This in turn has implications for our policymaking. Key policy insights Policymakers should explore how an understanding of approach informs climate change mitigation policymaking. Climate change mitigation policy communities should critically examine the underlying assumptions and worldviews that influence both how we encounter climate change mitigation and how we act upon it. An appreciation of 'approach' demands skills not typically valued or taught to climate change mitigation policymakers, with implications for climate change mitigation policy curricula and the composition of policymaking teams Complexity thinking opens up spaces for policymaking currently obscured by the dominant climate change mitigation policy approaches.